2018
DOI: 10.3390/ijerph15091899
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the International Classification of Functioning, Disability, and Health (ICF) Core Sets for Children and Youth with Cerebral Palsy: Global Initiatives Promoting Optimal Functioning

Abstract: Background: The International Classification of Functioning, Disability, and Health (ICF) Core Sets for children and youth with cerebral palsy (CP) offer service providers and stakeholders a specific framework to explore functioning and disability for assessment, treatment, evaluation, and policy purposes in a global context. Objective: Describe global initiatives applying the ICF Core Sets for children and youth with CP, with a focus on contributions to clinical practice and challenges in their implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 34 publications
(40 reference statements)
1
40
0
3
Order By: Relevance
“…On the other hand, Sciariti et.al. have proposed electronic implementation of International Classification of Functioning, Disability, and Health (ICF) Core Sets for children and youth with CP, arguing that ICF Core Sets for CP will be highly practicable in management of health services and in building profiles of functioning and disability for patients worldwide [60]. By recognising the needs of a child with CP and evaluating his/her functioning in the society it will be possible to facilitate management of services and to relieve the caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Sciariti et.al. have proposed electronic implementation of International Classification of Functioning, Disability, and Health (ICF) Core Sets for children and youth with CP, arguing that ICF Core Sets for CP will be highly practicable in management of health services and in building profiles of functioning and disability for patients worldwide [60]. By recognising the needs of a child with CP and evaluating his/her functioning in the society it will be possible to facilitate management of services and to relieve the caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) has two frameworks derived from the biopsychosocial model and related to comprehensive assessment of children's health and development: the International Classi cation of Functioning, Disability and Health for Children and Youth(ICF-CY) [15] and Nurturing Care [16]. The ICF-CY includes "health conditions," "body structures and functions," "activities and participation," "environmental (contextual)" and "personal" factors.The ICF-CY was a WHO approved "derived" classi cation but the two have now been merged and are referred to as ICF-CY to addressall aspects of functioning across the lifespan.Tools based on ICF-CY have involved children with disabilities [16], autism [17], cerebral palsy [18], and chronic illness [19]. The recently launched WHO Nurturing Care Framework [20] for young children includes "good health," "adequate nutrition," "responsive caregiving," "opportunities for early learning," and "security and safety."…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they have also shown that the curative effect of scalp acupuncture is correlated with the cerebral activating reaction in motor dysfunction in stroke patients [37,38] Based on the International Classification of Functioning, Disability, and Health (ICF), once the diagnosis of CP is ascertained or highly suspected, there are numerous tools to assess the impact of CP on different health-related domains, such as physical functioning, daily activities, quality of life, health-related quality of life, family well-being, education, and so on [43][44][45][46].Cerebral palsy rehabilitation evaluation plays an important role in the Cerebral Palsy rehabilitation clinical studies.…”
Section: Discussionmentioning
confidence: 99%